Assessing equity in transport accessibility to work and study: The Bogotá region. (January 2017) - Guzman, Luis A.; Oviedo, Daniel; Rivera, Carlos
Abstract: This research was aimed at exploring levels of equity in accessibility to employment and education in the city-region of Bogotá, Colombia's capital city. Building on consolidated methodologies for the assessment of potential accessibility, we estimate accessibility indicators at the zone level, evaluate how potential accessibility varies among income groups, and present evidence related to transport mode, in order to analyze social and spatial inequalities produced by the distribution of accessibility to employment and education activities. The research incorporates a method to evaluate how accessibility varies among zones according to average income and mode of transport in order to produce evidence-based arguments that can inform transport policy in the city-region of Bogotá, and other similar contexts in the Global South. Our results show strong distributional effects of the socio-spatial and economic structure of the city-region, its transport infrastructure and services, and the effect of current transport and land-use policies for citizens of different income groups. The tools and empirical evidence in this research seek to contribute to informed policy development in Latin America and other developing contexts, and feeding current debates on the role of accessibility in addressing social and spatial inequalities stemming from urban mobility.